JUSTIFICATION OF THE CHOICE OF THE SITE FOR STUDYING THE MORPHOLOGICAL COMPOSITION OF HOUSEHOLD WASTE - ILLIASH, ОKSANA; BREDUN, VIKTOR (Herald of Khmelnytskyi National University. Technical sciences, 2023)
Purpose. The research is designed to substantiate the choice of a territorial community in the territory of Poltava region, which is typical for the region regarding the processes of forming the morphological composition of household waste. Methodology. The work uses the methods of factor analysis of factors affecting the processes of forming the morphological composition of solid household waste in the conditions of territorial communities of the Poltava region. The results. The document defines nine criteria by which territorial communities are selected for research. These include: the type of settlement, the demographic composition of the settlement, the structure of development and the existing housing stock, architectural and planning features, features of the social and household system, the industrial specifics of the region, the structure of the communal economy, the existing waste collection system, the available equipment for garbage collection. On the basis of the specified criteria, the selection of the Kotelva territorial community as an object of research within the framework of the implementation of the Ukrainian-Austrian scientific project "Investigation of the composition of solid household waste and its resource potential" is substantiated. Originality. Methodological bases for the justification of the choice of territorial communities based on the processes of forming the morphological composition of solid household waste have been developed and tested. Practical value. The results of the study were used in the implementation of the Ukrainian-Austrian research project "Study of the composition of solid household waste and its resource potential" with the aim of increasing the efficiency of the regional waste management system.
Keywords: waste management system; morphological composition of waste; united community; criteria